Acute kidney injury in the pediatric intensive care unit at a tertiary care hospital of the Armed Forces: a cross-sectional observational study - Bajracharya, Punam (Med J Armed Forces India, 2020)
BACKGROUND: Acute kidney injury (AKI) is shown to be the commonest complication in critically ill children admitted to the pediatric intensive care unit (PICU). Kidney Disease: Improving Global Outcomes (KDIGO) classification and definition are now used universally. We undertook prospective observational study to study the etiology and maximum stage of AKI as defined by KDIGO and its complications and outcomes. METHODS: All children admitted to the PICU were included in the study. The diagnosis of sepsis and multiorgan dysfunction syndrome (MODS) was made according to the standard international guidelines. The patients were followed up till discharge/death. All children were screened for AKI at admission and subsequently using serum creatinine measured by modified Jaffe's method and urine output measurement. RESULTS: A total of 197 children were admitted to the PICU. 38 (19.28%) developed AKI, and 6 (15.78%) developed stage III AKI. Malignancies, serious neurological and renal disorders, and postsurgery complications accounted for most of the cases with AKI. Six were admitted with primary renal condition. Sepsis with or without MODS was seen in 12 patients with AKI and in 8 without AKI. Twenty-one children with AKI and 3 children without AKI were exposed to nephrotoxic drugs. Twenty-three children with AKI required inotropic support. The average length of stay (ALOS) of children with AKI in the PICU was 9.86 days, whereas ALOS of children without AKI was 6.23 days. Eighteen children with AKI (47.36%) and 36 (21.38%) with no AKI died. CONCLUSIONS: AKI in children in the PICUs of referral hospitals in the armed forces have varied etiologies and presentations. These children require early identification and management with close monitoring to prevent long-term renal morbidity and mortality.